1977
DOI: 10.1007/bf02097763
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture gas chromatographic determination of Kepone® residues in environmental samples

Abstract: The pollution of the environment with Kepone (decachlorooctahydro-1,3,4-metheno-2H-cyclobuta[cd]pentalen-2-one) by an industrial manufacturer of the pesticide resulted in the contamination of several terrestrial media, including biological life, near the entry of the insecticide into the ecosystem. The substrata investigated and for which residue methodology was developed included river sediment, soil, water, shellfish, and finfish. Rigorous extraction techniques utilizing the Soxhlet apparatus and the Polytro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Figure 3 shows the LH-20 GPC elution profiles of these Kepone derivatives and [14C]Kepone hydrate. Moseman et al (1977) reported that the addition of methanol to hexane solutions of Kepone increased the sensitivity of Kepone to EC-GC analysis. Methanol increases the solubility of Kepone in hexane.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the LH-20 GPC elution profiles of these Kepone derivatives and [14C]Kepone hydrate. Moseman et al (1977) reported that the addition of methanol to hexane solutions of Kepone increased the sensitivity of Kepone to EC-GC analysis. Methanol increases the solubility of Kepone in hexane.…”
Section: Resultsmentioning
confidence: 99%
“…Chlordecone (decachlorooctahydro‐1,3,2‐metheno‐2 H ‐cyclobuta[ c,d ]pentalen‐2‐one) is an organo‐chlorine insecticide that was formerly used extensively 1. The compound is a member of the persistent organic pollutants that exhibit remarkably long half‐lives in the environment, and it is well known that chlordecone shows various toxicities such as arrest of sperm maturation,2 blocking of reproductive function,3 and a variety of estrogen‐like effects on the female reproductive system in birds and mammals 4.…”
mentioning
confidence: 99%
“…Numerous studies, dedicated to the CLD determination in various matrixes has been conducted since 1960. Electron capture gas chromatography (GC-ECD) has become a technique of choice for the determination of CLD in water [4] and [5], soil and sediments [5], [6] and [7] food [8] and biological tissues [9] and [10]. More recently gas chromatography equipped with mass spectrometry has also been employed for CLD determination (GC-MS).…”
Section: Introductionmentioning
confidence: 99%